The Role of the Economic Dimension in Conflict Prevention in Europe - Daniel Dăianu (Romanian Journal of European Affairs)
The article was originally delivered as a discourse at the UNECE/OSCE International Conference “The Role of the Economic Dimension in Conflict Prevention in Europe”, Villars, Switzerland, November 19, 2001. It therefore attempts at a reexamination of the economic and environmental dimension of security, emphasizing the urgent need of maximizing the effort of identifying security risks and tackling them in terms of early warning and conflict prevention. Due to the specific initial format of the text, minor editing has been operated.